Gratification towards weather information via television: an analysis of the coastal communities in Malaysia - Mohamed Yusof, Zaim Fahmi; Kamaruddin, Nurani; Omar, Siti Zobidah; Bolong, Jusang; D`Silva, Jeffrey Lawrence; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2014)
The main purpose of this study is to determine Malaysian coastal communities gratification towards weather information via television. The study was a quantitative study where a developed instrument was used as the main data collection tool. Through, multi-stage simple random sampling, a total of 210 coastal villagers from 3 coastal areas in Malaysia were selected as the respondents. The findings demonstrate that there was a gap between the weather information received and the weather information needed by the respondents, as well as a gap between the weather information received and the weather information believed. A number of discussions are highlighted in this study in the hope that they can assist the appropriate parties in generating the best strategy for information sharing and dissemination processes among the coastal communities.